Brisingr - Paolini, Christopher (New York : Alfred A. Knopf, 2008)
The further adventures of Eragon and his dragon Saphira as they continue to aid the Varden in the struggle against the evil king, Galbatorix.
Keywords: Fantasy; Dragons -- Fiction; Youth's writings